"The threat is in the head, not in the legs": Activating negative age stereotypes generates extra cognitive load during walking. (November 2020) - Chalabaev, Aïna; Palluel, Estelle; Ruchaud, François
Abstract: Objective: Activating negative age stereotypes has been consistently shown to impair cognitive performance in older adults, but not motor performance, especially on mobility tasks. We tested the hypothesis that older adults may still experience stereotype threat, even if mobility performance is not affected. To do so, we examined whether inducing negative stereotypes may increase cognitive load during a walking task. Method: This question was investigated in a dual-task paradigm: older adults performed simultaneously a walking task and a Stroop task, in stereotype and control conditions. Results: Results showed that the stereotype induction did not affect walking parameters but decreased performance on the Stroop task, indicating that this induction increased cognitive load during walking. Discussion: These results suggest that negative age stereotypes may be damaging even if walking parameters are not affected, by altering older adults' attention to their walking environment. We conclude by highlighting theoretical and practical implications. Highlights: Activating negative age stereotypes impaired Stroop performance during walking. Activating negative age stereotypes did not impair walking performance. Results suggest stereotype threat occurs even if motor performance is unaffected. Data were analyzed using linear mixed models to reduce risk of Type I error.